Analisis Kesehatan Mental pada Remaja: Literatur Review - Silvina Maha; Isnaini Sohna Simangunsong; Marniati Marniati (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
The mental state of young people is a crucial issue which has a major effect on the level of life and progress of next generation in Indonesia. This research seeks to explore the aspects that influence young people's mental state through a review of 30 scientific papers published between 2015 and 2024. The findings of the analysis show that young people's mental state is influenced by a variety of internal elements, such as emotion regulation, religious beliefs and gratitude, as well as external factors such as family circumstances, support from friends, neighbourhood environment, social media habits and experiences of being bullied. Excessive use of social media and being a victim of bullying were found to increase the potential for mental problems, such as anxiety, depression and mental distress. In contrast, support from family and friends, as well as a community-based education intervention agenda, play an important role in strengthening adolescents' psychological resilience. This research underscores the urgency of a comprehensive collaborative approach involving many parties, including families, educational institutions, the wider community, and the government, to sustainably improve the mental health of adolescents in Indonesia.